Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s10620-008-0500-y
|View full text |Cite
|
Sign up to set email alerts
|

Poor Response to Pegylated Interferon and Ribavirin in Older Women Infected with Hepatitis C Virus of Genotype 1b in High Viral Loads

Abstract: Response to combined PEG-IFN and ribavirin is poorer in female than male patients with hepatitis C who are aged >or=50 years, irrespective of compliance with treatment. Low estrogen levels in older women could be responsible for their impaired response to PEG-IFN and ribavirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 41 publications
8
60
1
Order By: Relevance
“…In assessment of the relationship of certain factors to relapse and SVR in patients with thrombocytopenia, we found that male gender didn't significantly differ from female gender and this was in agreement with Sezaki et al [16] who reported that the difference in response to treatment in chronic HCV according to sex is controversial.…”
Section: Discussionsupporting
confidence: 90%
“…In assessment of the relationship of certain factors to relapse and SVR in patients with thrombocytopenia, we found that male gender didn't significantly differ from female gender and this was in agreement with Sezaki et al [16] who reported that the difference in response to treatment in chronic HCV according to sex is controversial.…”
Section: Discussionsupporting
confidence: 90%
“…It is possible that the higher prevalence of viral clearance among women is associated with immunological factors 12 and genetics (in particular, the HLA DRB1*01 13 , HLA-Bw35, HLA-DRB1*8 14 and GG genotypes 15 ). To date, the only study that evaluated the influence of gender on the treatment for chronic hepatitis C genotype 1 concluded that the response to combined therapy with pegylated interferon alpha (Peg-IFN) and ribavirin (RBV) was poorer among female than among male hepatitis C-infected patients aged 50 years or older, irrespective of compliance (32% vs 63%) 16 . Previously, Hayashi et al assessed gender importance in relation to the response to conventional interferon alpha treatment (IFN) alone and concluded that women younger than 40 years of age had higher rates of sustained virological response (SVR) than did men (75% vs 33%) 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators found female gender as the positive predictor for SVR in RCT and in "real life condition"studies [9,24,25,56,63,64]. The others did not confirm these results [20,40,42,44,65], or even found that response to combined treatment and SVR in females 50 years old or older was poorer than in males [66]. Low estrogens level in older women could be responsible for their impaired response to antiviral treatment.…”
Section: Discussionmentioning
confidence: 99%